22.3k views
3 votes
HELPPPPPPPPP and explain why

HELPPPPPPPPP and explain why-example-1

2 Answers

4 votes


{x}^(2) + 5x \\ x(x + 5)
notice there's no whole number in front of the x^2, so no number can factor out both terms, but both have at least one x, so one x factors out of both
User DSteman
by
6.3k points
4 votes
Answer: True

=================================================

x^2 = x*x
5x = 5*x
Both x^2 and 5x have a factor of x in common

x^2 + 5x = x*x + 5*x
x^2 + 5x = x*x + x*5
x^2 + 5x = x*(x+5) .... use the distributive property in reverse

x^2 + 5x factors to x*(x+5)

As a way to check, you can distribute the x back in
x*(x+5) = x*x + x*5
x*(x+5) = x^2 + 5x
and we get the original expression again
User Yedpodtrzitko
by
6.0k points